The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-70707-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic heating of nanoparticles as a scalable cryopreservation technology for human induced pluripotent stem cells

Abstract: Scale-up of production is needed for industrial applications and clinical translation of human induced pluripotent stem cells (hiPSCs). However, in cryopreservation of hiPSCs, successful rewarming of vitrified cells can only be achieved by convective warming of small volumes (generally 0.2 mL). Here, we present a scalable nano-warming technology for hiPSC cryopreservation employing inductive heating of magnetic nanoparticles under an alternating magnetic field. The conventional method by water bath heating at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Nanowarming exploits the local heating effect associated with magnetic nanoparticles in an alternating magnetic field, allowing homogeneous and rapid rewarming. Application of mesoporous silica-coated iron oxide nanoparticles have aided the cryopreservation of porcine arterial tissue (20 ml volume) 39 and magnetite (Fe 3 O 4 ) nanoparticles increased the cell viability of human induced pluripotent stem cells (hiPSCs) to 74.8% compared with 38.5% as assessed immediately post-thaw by Hoechst/SYTOX green staining 40 . Microporous silicon-coated iron oxide nanoparticles improved cryopreservation outcomes with samples as large as rat kidneys 41 .…”
Section: Chemical Tools For Cryopreservationmentioning
confidence: 99%
“…Nanowarming exploits the local heating effect associated with magnetic nanoparticles in an alternating magnetic field, allowing homogeneous and rapid rewarming. Application of mesoporous silica-coated iron oxide nanoparticles have aided the cryopreservation of porcine arterial tissue (20 ml volume) 39 and magnetite (Fe 3 O 4 ) nanoparticles increased the cell viability of human induced pluripotent stem cells (hiPSCs) to 74.8% compared with 38.5% as assessed immediately post-thaw by Hoechst/SYTOX green staining 40 . Microporous silicon-coated iron oxide nanoparticles improved cryopreservation outcomes with samples as large as rat kidneys 41 .…”
Section: Chemical Tools For Cryopreservationmentioning
confidence: 99%
“…[13] More recently, Horie et al showed that human induced pluripotent stem cells (and cell aggregates) could be successfully vitrified and rewarmed with high viabilities in scaled up 20 mL CPA systems using RF nanowarming. [14] Using differential scanning calorimetry experiments, Xu et al showed that the presence of magnetic nanoparticles in CPA suppresses ice nucleation and growth during cooling and rewarming. [15] In parallel computational modeling efforts, Solanki et al and Eisenberg et al provide detailed analysis of the thermomechanical stresses during cooling and nanowarming in CPA solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic vials are the most commonly used cryopreservation container, and their combination with water bath rewarming is currently considered the gold standard for the cryopreservation of most biological samples. However, cryogenic vials combined with convective rewarming can achieve a rewarming rate of only about ∼160 °C/min . This slow rewarming rate makes it possible for ice crystals to grow completely during the rewarming process, thus causing severe ice crystal damage to biological samples.…”
Section: Resultsmentioning
confidence: 99%